Prevalence and zoonotic potential of Enterocytozoon bieneusi and Giardia duodenalis in dairy cattle from Anhui Province, China - Li, Falei; Cheng, Shimei; He, Chaoyue; Meng, Libing; Wang, Aihong; Shao, Meng; Xu, Gaoxiao; Zhang, Huilin (Frontiers in Veterinary Science, 2025)
IntroductionEnterocytozoon bieneusi (E. bieneusi) and Giardia duodenalis (G. duodenalis) are common intestinal pathogens in humans and farmed animals. There is limited data available on the positivity rates and genetic identity of E. bieneusi and G. duodenalis in dairy cattle from Anhui, China.MethodsTo understand the transmission of E. bieneusi and G. duodenalis in these animals, a total of 1,043 fecal samples were collected from cattle on five farms (Fuyang, Huainan, Huaibei, Bengbu, and Jieshou) in Anhui province of China between May 2023 and August 2024. The G. duodenalis in fecal samples was detected by nested PCR targeting a 511-bp fragment of the β-giardin (bg) gene, a 599-bp fragment of the glutamate dehydrogenase (gdh) gene, and a 530-bp fragment of the triosephosphate isomerase (tpi) gene. The E. bieneusi was detected by nested PCR targeting a 392-bp fragment of the internal transcribed spacer (ITS) of the rRNA gene.ResultsThe PCR analysis revealed positivity rates of 29.7% (310/1043) for E. bieneusi and 2.8% (29/1043) for G. duodenalis. The cattle from the Bengbu farm had significantly higher positivity rates of E. bieneusi than Fuyang, Huainan, and Huaibei farms (χ2 = 61.6, df = 1, p < 0.0001; χ2 = 76.4, df = 1, p < 0.0001; χ2 = 20.6, df = 1, p < 0.0001). A total of 11 known genotypes of E. bieneusi have been identified: J (n = 154), BEB4 (n = 76), I (n = 63), CGC1 (n = 8), N (n = 2), BEB8 (n = 2), ALP1 (n = 1), BLC13 (n = 1), CHC13 (n = 1), CHN6 (n = 1), and D (n = 1). Additionally, two genotypes of G. duodenalis have been identified, including assemblage A (n = 6) and assemblage E (n = 23).DiscussionThe results indicate that known zoonotic E. bieneusi and G. duodenalis are prevalent in dairy cattle, thereby enhancing our understanding of the genetic diversity and transmission of these pathogens in these animals.